Optimism and pessimism. Associated variables in the school context - Díez González, Antonio (Pulso. Revista de educación, 2004)
Advocating for silence as a viable option without it being perceived as avoidance or escapism from society’s actual issues will prove to be challenging. The following lines delve into the essence and endeavours of the Social Educator, emerging from the reality of silence. Within a brief span, silence has evolved from being a commonplace occurrence to a rare and commercialised commodity, or simply another item to be consumed. It would be disheartening if the Social Educator were to overlook such a significant challenge and resort to the harshest punishment of all, oblivion.